Igba-Ada Festival: Commemorating the Ohafia Invaders as a Kind of Traditional Carnival through Ovala Festival in Aguleri Cosmology - Madukasi Francis Chuks (RIRAI Publisher, 2020)
The ritual festival of Igba-Ada is a traditional carnival which symbolizes commemoration of the synergy between the living and dead and it acts as a spiritual conduit that binds or compensates the entire villages that constitutes Aguleri as a kingdom of one people with one destiny through the mediation of their contact with their ancestral home and with the built/support in religious rituals and cultural security of their extended brotherhood. This research work discusses Mmanwu Festivals and their symbolic representation in an Igbo community focusing on Igba-Ada carnival in Aguleri, Anambra East local government area. Secondary source as a kind method were reviewed and analyzed using the area cultural approach. This festival is a commemoration of how the Ohafia invaders were chased out and conquered by the egalitarian youths of Aguleri by reinenforcing themselves in other to wage war against their enemies. Basically, it usually an occasion for jocundity and thanksgiving; people appear in their best through mimic forms and give of their best. The carnival reunites their intimate brotherhood and shows how the Aguleri community uses this through the mediation of its rituals to reassert or validate the continuity and existence of Aguleri [Igbo] Traditional Religion. It is very significant in the sense that at the conclusion of the Igba-Ada carnival, the King acquires the symbolic and political authority to rule and the power to face his enemies and symbolically preserve his realm.